2004
DOI: 10.1128/aem.70.2.1088-1096.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sourdough Bread Made from Wheat and Nontoxic Flours and Started with Selected Lactobacilli Is Tolerated in Celiac Sprue Patients

Abstract: This work was aimed at producing a sourdough bread that is tolerated by celiac sprue (CS) patients. Selected sourdough lactobacilli had specialized peptidases capable of hydrolyzing Pro-rich peptides, including the 33-mer peptide, the most potent inducer of gut-derived human T-cell lines in CS patients. This epitope, the most important in CS, was hydrolyzed completely after treatment with cells and their cytoplasmic extracts (CE). A sourdough made from a mixture of wheat (30%) and nontoxic oat, millet, and buc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(171 citation statements)
references
References 44 publications
3
158
2
Order By: Relevance
“…This difference was more pronounced when peptides were added to the dough. Similar observations have been made by Corsetti et al and Di Cagno et al (6,10), who reported that sourdough fermentation results in a more complete degradation of peptides than an aseptic acidifed dough. This implies that the difference between L. sanfranciscensis-fermented doughs and aseptic acidified doughs depends on a synergistic effect between flour proteinases and the peptide metabolism of L. sanfranciscensis.…”
Section: Discussionsupporting
confidence: 76%
“…This difference was more pronounced when peptides were added to the dough. Similar observations have been made by Corsetti et al and Di Cagno et al (6,10), who reported that sourdough fermentation results in a more complete degradation of peptides than an aseptic acidifed dough. This implies that the difference between L. sanfranciscensis-fermented doughs and aseptic acidified doughs depends on a synergistic effect between flour proteinases and the peptide metabolism of L. sanfranciscensis.…”
Section: Discussionsupporting
confidence: 76%
“…14G, Lactobacillus sanfranciscensis 7A, and Lactobacillus hilgardii 51B were previously selected based on their capacity to hydrolyze gliadins (14). L. sanfranciscensis LS3, LS10, LS19, LS23, LS38, and LS47 were selected based on their peptidase systems, with particular reference to activities toward Pro-rich peptides (12).…”
Section: Microorganisms Lactobacillus Alimentarius 15 M Lactobacillmentioning
confidence: 99%
“…This challenge thrown at the scientific world is well received and currently there is burgeoning research with a 'thirst to quench hunger'. At present there is considerable interest in the consumption of alternative crops such as buckwheat, oats, barley, spelt, rye as potential recipes for healthy food having special dietary uses (Skrabanja et al 2001a;Di Cagno et al 2004). The use of these pseudo cereals is of great nutritional interest because of their peculiar composition (Skrabanja et al 2001b;Abdel-Aal and Hucl 2002;Gabrovska et al 2002;Kim et al 2004).…”
Section: Introductionmentioning
confidence: 99%